2009
DOI: 10.1021/jf901897f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Activity of Isoindoline-1,3-dione Substituted Benzoxazinone Derivatives Containing a Carboxylic Ester Group

Abstract: A carboxylic ester group was introduced to three series of isoindolinedione substituted benzoxazinone derivatives. Some of these analogues exhibited good herbicidal activities, and the injury symptoms against weeds included leaf cupping, crinkling, bronzing, and necrosis, typical of protox inhibitor herbicides. Structurally, they were classified as Chemical Group A (4-carboxylic ester group-6-isoindolinyl-benzoxazinones), B (4-carboxylic ester group-7-isoindolinyl-benzoxazinones), and C (4-carboxylic ester gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…To obtain novel PPO inhibitors, a series of N -phenyl phthalimides were designed by molecular docking using the mt PPO as a target, and by using Flumioxazin as a lead (Figure 1) [22,23], after which they were synthesized and characterized by NMR and High resolution mass spectrometry (HR-MS). Their herbicidal activities were also evaluated against Brassica campestris ( B. campestris ), Amaranthus retroflexus ( A. retroflexus ) and Digitaria sanguinalis ( D. sanguinalis ) to verify our molecular design strategy.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain novel PPO inhibitors, a series of N -phenyl phthalimides were designed by molecular docking using the mt PPO as a target, and by using Flumioxazin as a lead (Figure 1) [22,23], after which they were synthesized and characterized by NMR and High resolution mass spectrometry (HR-MS). Their herbicidal activities were also evaluated against Brassica campestris ( B. campestris ), Amaranthus retroflexus ( A. retroflexus ) and Digitaria sanguinalis ( D. sanguinalis ) to verify our molecular design strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Some, such as compound A (Scheme ), displayed both promising inhibitory activity against protoporphyrinogen oxidase in vitro (IC 50 = 9.50 nM) and excellent herbicidal activity against sensitive plant species at an application rate of 93.75 g/ha. It was also demonstrated that the core structure, 2H ‐1,4‐benzoxazin‐3‐(4 H )‐one, was an important pharmacophore of this PPO herbicide series . As a continuation of our work with this structural motif, we designed a series of novel HPPD inhibitors, 2‐(2 H ‐benzo[ b ] [1,4]oxazine‐7‐carbonyl)cyclohexane‐1,3‐dione analogs ( B ) (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that the core structure, 2H-1,4-benzoxazin-3-(4H)-one, was an important pharmacophore of this PPO herbicide series. [18][19][20] As a continuation of our work with this structural motif, we designed a series of novel HPPD inhibitors, 2-(2H-benzo[b] [1,4]oxazine-7carbonyl)cyclohexane-1,3-dione analogs (B) (Scheme 1). The synthesis, HPPD inhibition and herbicidal activity of these analogs are described.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-containing heterocyclic compounds have maintained the interest of researchers through decades of historical development of organic synthesis. Among the nitrogen heterocycles, 1,4-benzoxazine is the important scaffold present in various agrochemicals and primarily used by plants as natural defense chemicals [2,3]. In particular, the utility of the 2H-1,4-benzoxazin-3-(4H)-one scaffold as a privileged structure for the generation of drug-like libraries in drug-discovery programs has been amply demonstrated.…”
Section: Introductionmentioning
confidence: 99%